Validity and reliability of the power slap board as an application to measure upper body vertical pulling power for female water polo players - Lim, C.; Wee, J.; Lee, M.; Lim, S.; Leow, S. (The Journal of Strength and Conditioning Research, 2024)
This study examined the validity and reliability of the power slap test (PS) as an assessment for upper body pulling power to predict water polo functional performance and competitive experience of female water polo players. Seventeen female water polo players from the national and development squads were recruited. Subjects completed test-retest sessions of PS testing and 1 session of functional performance tests for the 15-m arms-only sprint (15 mAOS) and the 5-m maximum shooting velocity (5 mMSV). All PS, 15 mAOS and 5 mMSV results were compared for predictability. Power slap scores demonstrated high reliability for left PS (intraclass correlations [ICC]: 0.96, 90% confidence interval [CI]: 0.91-0.98), right PS (ICC: 0.96, 90% CI: 0.90-0.98), left and right center of mass (COM) displacement (ICC: 0.98, 90% CI: 0.96-0.99; ICC: 0.95, 90% CI: 0.88-0.98), and summed PS (ICC: 0.96, 90% CI: 0.92-0.99). All absolute PS scores and left COM displacement (COMdispL) demonstrated large correlations with the 15 mAOS times (r = -0.542 to -0.52, r2 = 0.27-0.29, p < 0.05). No performance parameters of the PS were correlated with the 5 mMSV performance (p > 0.05). This study validates the reliability of the PS as a dryland assessment tool for upper body pulling power. Only absolute PS scores and COMdisp were validated as weak predictors of the arms-only sprint times over 15 m. Its predictive power significantly improved when considered in combination with shooting performance. All absolute and normalized kinetic and kinematic PS parameters did not predict functional performance and competitive experience.